Assessment of the effect of 21-day head-down bed rest on the cardiovascular system by blood protein composition - Kashirina, Daria N.; Pastushkova, Ludmila Kh.; Goncharova, Anna G.; Larina, Irina M. (Frontiers in Physiology, 2024)
Head-down bed rest (HDBR) is one of the models of the physiological effects of weightlessness used, among other things, to assess the effect of hypokinesia on the physiological systems of the human body and, first of all, on the cardiovascular system. The aim of the work was to study the effect of 21 days of HDBR factors on the cardiovascular system based on blood proteomic profile data. It was revealed that HDBR conditions led to an increase in the levels of proteins of the complement and the coagulation cascade systems, platelet degranulation, fibrinolysis, acute phase proteins, post-translational modification of proteins, retinol-binding protein 4 (RBP4), apolipoprotein B, which are associated with cardiovascular diseases, and other proteins that affect the functions of endothelial cells. Blood levels of proteins involved in cytoskeletal remodelling, oxygen transport, heme catabolism, etc. have been shown to decrease during HDBR.